The importance of recognition in the organizations: Notes for the creation of the award "Master of Neurosurgery" - Mezzadri, Juan Jose (Revista Argentina de Neurocirugía, 2021)
The objective of this publication is to create the conditions for the award "Master of Neurosurgery". For the recognition of a person, the relevance of their actions by virtue of their contributions to an organization are taken into account. The respect that recognition gives us is what increases our self-esteem. For job recognition, a simple thank you is not enough. It is necessary to create a space where everyone can develop their interests and achieve their objectives and make available everything necessary to facilitate and simplify the work. The purpose recognition as master is to highlight a vital career in the practice of a medical specialty. The award would be a reward given for some merit or service, to highlight those values ​​that allowed the development of the specialty, recognize their commitment, distinguish the effort made in the training of human resources and value technical-scientific achievements.
Keywords: award – organization – recognition